A small molecule transcription factor EB activator ameliorates beta‐amyloid precursor protein and Tau pathology in Alzheimer's disease models. Issue 2 (19th December 2019) - Song, Ju‐Xian; Malampati, Sandeep; Zeng, Yu; Durairajan, Siva Sundara Kumar; Yang, Chuan‐Bin; Tong, Benjamin Chun‐Kit; Iyaswamy, Ashok; Shang, Wen‐Bin; Sreenivasmurthy, Sravan Gopalkrishnashetty; Zhu, Zhou; Cheung, King‐Ho; Lu, Jia‐Hong; et al.
Abstract: Accumulating studies have suggested that targeting transcription factor EB (TFEB), an essential regulator of autophagy‐lysosomal pathway (ALP), is promising for the treatment of neurodegenerative disorders, including Alzheimer's disease (AD). However, potent and specific small molecule TFEB activators are not available at present. Previously, we identified a novel TFEB activator named curcumin analog C1 which directly binds to and activates TFEB. In this study, we systematically investigated the efficacy of curcumin analog C1 in three AD animal models that represent beta‐amyloid precursor protein (APP) pathology (5xFAD mice), tauopathy (P301S mice) and the APP/Tau combined pathology (3xTg‐AD mice). We found that C1 efficiently activated TFEB, enhanced autophagy and lysosomal activity, and reduced APP, APP C‐terminal fragments (CTF‐β/α), β‐amyloid peptides and Tau aggregates in these models accompanied by improved synaptic and cognitive function. Knockdown of TFEB and inhibition of lysosomal activity significantly inhibited the effects of C1 on APP and Tau degradation in vitro. In summary, curcumin analog C1 is a potent TFEB activator with promise for the prevention or treatment of AD. Abstract : A small molecule activator of transcription factor EB (TFEB) promotes the degradation of beta‐amyloid precursor protein (APP) fragments, β‐amyloid peptides (Aβ), and phosphorylated MAPT/Tau aggregates in three transgenic mice models of Alzheimer's disease (P301S, 5xFAD, and 3xTg) and prevents memory impairments.